Nutritional status of children in a malaria meso endemic area: cross sectional study on prevalence, intensity, predictors, influence on malaria parasitaemia and anaemia severity - Sumbele, Irene Ule Ngole (BMC Public Health, 2015)
BACKGROUND: The contradictory results on the interaction between nutritional status and malaria warrants further investigation in various epidemiological settings, to assert the antagonistic or synergistic relationship. This study examines the prevalence, severity and predictors of malnutrition and its influence on malaria parasitaemia and anaemia severity in children in the Mount Cameroon area. METHODS: A cross-sectional study involving 454 children ≤ 14 years was carried out from February to May 2013 in Muea community. Anthropometric measures of malnutrition (z-scores < −2 standard deviations below mean) were obtained and spleen size assessed. The prevalence and density of malaria parasites were determined and haemoglobin concentration and white blood cell count obtained using an automated haematology analyzer. Univariate and multivariate analyses were used to evaluate influence of malnutrition on anaemia, malaria parasitaemia and predictors respectively. RESULTS: The overall prevalence of malnutrition was 22.8 %, with stunting being the most common form (17.1 %), followed by underweight (8.2 %) and wasting (5.5 %). Stunting was significantly higher (P < 0.01) in males (23.1 %) than in females (11.9 %). The prevalence of malnutrition was significantly highest (P = 0.03) in children ≤5 years old (29.5 %) than their counterparts. Severe stunting, wasting and underweight were prevalent in 4.9 %, 1.6 % and 1.8 % of the children respectively. Clinical malaria parasitaemia was significantly higher (P = 0.01) in children who were stunted (16.9 %) and underweight (21.6 %) than their normal counterparts (7.5 %; 8.2 % respectively). The model demonstrated sex (P = 0.006) and age group 1.1-3 years (P = 0.03) as significant predictors of malnutrition. In children who were malaria parasite negative, the prevalence of anaemia as well as severities were significantly higher (P = 0.04 and P = 0.001 respectively) in those malnourished. CONCLUSIONS: The presence of stunting in the community significantly augmented the prevalence and clinical presentation of Plasmodium infection. Malnutrition enhanced the severity of anaemia in malaria parasite negative children hence, their health and growth potential needs to be improved upon.